Domestic violence during pregnancy: a neglected and unseen public health problem - Shidhaye, Pallavi R.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
According to World Health Organisation (WHO), domestic violence (DV) is defined as psychological/emotional, physical, or sexual violence, or threats of physical or sexual violence that are inflicted on a woman by a family member: an intimate male partner, marital/cohabiting partner, parents, siblings, or a person very well known within the family or a significant other (i.e. former partner) when such violence often takes place in the home. Intimate partner violence (IPV) and sexual violence against women are major public health problems and violations of human rights. They result in serious short- and long-term physical, sexual and reproductive, and mental health problems, including increased vulnerability to HIV. Near about 15-71% of women experience physical and/or sexual violence by an intimate partner at some point in their lives. Violence against women (VAW) affects all phases of lifecycle of a women, as rightly pointed out by WHO, starting from sex selective abortion in prebirth period; female infanticide, female genital mutilation, child marriage or prostitution in childhood; physical, sexual, psychological abuse, rape, sexual harassment, dowry murders, forced pregnancy in adolescence and adulthood period; ending in physical and psychological abuse in elderly.